Recomendações para trabalhadores na multidão superarem barreiras em projetos de software crowdsourcing - Zanatta, Alexandre Lazaretti (2018)
Software crowdsourcing development platforms require a continuous influx of crowdworkers for their continuity. Crowdworkers should be encouraged to play an important role in the online communities by being active members, but they face difficulties when attempting to participate. For this reason, we investigated the difficulties that crowdworkers face in crowdsourcing software development platforms. We conducted empirical studies relying on multiple data sources and research methods including literature review, peer review, field study, and procedures of grounded theory. We observed that crowdworkers face many barriers – related to competence, collaboration, and time management – when making their contributions in software crowdsourcing development, which can result in dropouts. Based on the identified barriers, literature review and, crowdworkers suggestions, we list 13 recommendations for participants as potential solutions to overcome such barriers. The recommendations were evaluated by surveying software crowdsourcing experts. The main contributions of this dissertation are a) empirical identification of barriers faced by crowdsourcing software development crowdworkers; and b) recommendations on how to minimize the barriers. We conclude that the crowdworkers need competency and an efficient time management effort to take part collaboratively in tasks of the Competition-Based Crowdsourcing Software Development of the Topcoder platform.